2016
DOI: 10.1186/s12885-016-2353-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically maintained SW13+ and SW13- subtypes have different oncogenic potential and convert with HDAC1 inhibition

Abstract: BackgroundThe BRM and BRG1 tumor suppressor genes are mutually exclusive ATPase subunits of the SWI/SNF chromatin remodeling complex. The human adrenal carcinoma SW13 cell line can switch between a subtype which expresses these subunits, SW13+, and one that expresses neither subunit, SW13-. Loss of BRM expression occurs post-transcriptionally and can be restored via histone deacetylase (HDAC) inhibition. However, most previously used HDAC inhibitors are toxic and broad-spectrum, providing little insight into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…However, this is consistent with the epigenetically plastic nature of SW13 cells and previous observation that ∼2–3% of the SW13 cell population will spontaneously transition to a mesenchymal phenotype under standard culture conditions [ 8 ]. Notably, not all cells treated with FK228 for 48 h expressed vimentin, but we have previously shown that it takes 72 h to achieve 100% conversion of the entire SW13 cell population to the SW13+ phenotype [ 9 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is consistent with the epigenetically plastic nature of SW13 cells and previous observation that ∼2–3% of the SW13 cell population will spontaneously transition to a mesenchymal phenotype under standard culture conditions [ 8 ]. Notably, not all cells treated with FK228 for 48 h expressed vimentin, but we have previously shown that it takes 72 h to achieve 100% conversion of the entire SW13 cell population to the SW13+ phenotype [ 9 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, ∼2% of the cells in culture exist as a slow growing, highly invasive, mesenchymal-like subtype that expresses SMARCA2 and the mesenchymal markers vimentin and CD44 and are referred to as SW13+ cells [ 8 ]. Intriguingly, HDAC inhibition can induce a phenotype transition from the tumorigenic SW13- to the metastatic SW13+, and the conversion can be confirmed by morphological changes and induction of SMARCA2 expression [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zager and Johnson have shown that during renal ischemia-reperfusion injury, enhanced binding of BRG1 to gene promoters is paralleled by progressive elevations of H3K4 methylation although it remains undetermined whether there is a cause-effect relationship [28] . Davis et al have reported that treatment of the BRG1 null SW-13 cells with HDAC inhibitors restores BRG1 expression and at the same time stimulates H3K4 hypermethylation [29] .We have previously shown that BRG1 is essential in maintaining H3K4 methylation on the endothelin (ET-1) gene promoter, likely through interacting with WDR5, in response to angiotensin II stimulation [22] . These data clearly establish a role for BRG1 in regulating locus-specific H3K4 methylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, many consequences are downstream of transcription factors and are therefore more difficult to characterize. For instance, treatment with HDAC inhibitors changes histone methylation [ 63 , 64 ], adding to the effect of acetylation on the binding of chromatin regulatory complexes (reviewed in [ 62 ]). Thus, much more characterization of the targets and consequences of acetylation must be completed.…”
Section: Histone Deacetylase (Hdac) Inhibitorsmentioning
confidence: 99%
“…Similarly, HDAC inhibitors have been proven to be effective in restoring the expression of the mutually exclusive, catalytically active subunits of the SWI/SNF complex, BRM and BRG1, which are silenced in nearly 20% of all cancers [ 92 94 ]. However, the therapeutic utility of restoring BRM and BRG1 expression via HDAC inhibition is still in question as in vitro work has demonstrated that while reexpression of these proteins does slow cancer cell growth, it also promotes metastatic traits [ 63 ].…”
Section: Histone Deacetylase (Hdac) Inhibitorsmentioning
confidence: 99%